Performance and Formation Mechanism of Trainee Teachers' Teaching Anxiety: Based on Spinoza's Theory of Affection - TIAN Guoxiu; LIU Tian (Jiaoshi jiaoyu xuebao)
In recent years, teachers' teaching anxiety has been widely concerned, while the teaching anxiety of trainee teachers has been rarely studied. Based on Spinoza's affection theory, this study takes semi-structured interview to collect data, and dynamically analyzes the emotional performance and the formation mechanism of trainee teachers' teaching anxiety in combination with programmed root theory and Nvivo11 Plus software. It is found that the teaching anxiety experienced by trainee teachers in teaching practice is mainly manifested as "fear" and "self-shame", which is the intuitive response of trainee teachers stimulated by the external environment and the change of conceptual power. Further tracing, it reveals that the root cause of trainee teachers' teaching anxiety lies in the asymmetric and unbalanced relationship between individuals and the environment, that is, trainee teachers are often in a relatively weak position in the complex and changeable educational environment, and this asymmetry exacerbates their inner anxiety. Therefore, the trainee teachers should enrich themselves, especially with the fulfillment of concepts that trainee teachers should face up to the inevitability of anxiety, replacing simple imagination with the knowledge of necessity; analyze the generationof anxiety, substituting fuzzy cognition with clear idea; lock the transformation node of anxiety, transcending the single perspective with multiple thinking; formulate the guiding creed of anxiety, turning the imagination sequenceinto rational order; seek the absolute restraint of anxiety, pursuing the ultimate love of education.